If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -8 = 36 + -2x + 4 Reorder the terms: -8 + -8x = 36 + -2x + 4 Reorder the terms: -8 + -8x = 36 + 4 + -2x Combine like terms: 36 + 4 = 40 -8 + -8x = 40 + -2x Solving -8 + -8x = 40 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -8 + -8x + 2x = 40 + -2x + 2x Combine like terms: -8x + 2x = -6x -8 + -6x = 40 + -2x + 2x Combine like terms: -2x + 2x = 0 -8 + -6x = 40 + 0 -8 + -6x = 40 Add '8' to each side of the equation. -8 + 8 + -6x = 40 + 8 Combine like terms: -8 + 8 = 0 0 + -6x = 40 + 8 -6x = 40 + 8 Combine like terms: 40 + 8 = 48 -6x = 48 Divide each side by '-6'. x = -8 Simplifying x = -8
| 95-7x=38x+20 | | -5(20v-68)=90(v-30) | | 11(-11v+5)=6(1-12v) | | 2x+3=8x+1 | | 4x-6(7-x)=6 | | -6(x+3)-10=21+5 | | 38(63x+56)=32(76x+19) | | 4x+20=44-2x | | 4(x+1)=12+8x | | 11+0.16=20 | | 12-8x=93-29x | | -2x-32(1+9x)=-32(1-25x) | | M*20=340 | | -6(1-5n)=-6-8n | | x/28=1/4 | | y=34x | | 4(x-2)=3(x+9) | | 3(x+3)=2(x-17) | | x-3=4x-5 | | 2*x^2+60x+800=0 | | 10(x-1)+3(x+5)=44 | | -2(2+8x)+7=-16+3x | | 53-h=42 | | 5(y+1)=20 | | -28+31+(-3)-8= | | 3(X+1)+2x=53 | | 9r^3+18r^2=72r | | 2x+56=4x+19 | | 10x-19=x+17 | | 3x+21+4x=42 | | 11+2(3m-10)=5(4-m) | | 4x^3+8x^3= |